Pengaturan Sanksi Kebiri Kimia Bagi Pelaku Pedofilia Berdasarkan Undang-Undang Perlindungan Anak - Ni Luh Bella Mega Brawanti; I Ketut Rai Setiabudi (Fakultas Hukum, Universitas Warmadewa, 2022)
The qualification of chemical castration sanctions in the Child Protection Law as an action sanction gives rise to a blur in viewing the purpose of chemical castration sanctions. In this writing, it seeks to clarify the difference between criminal sanctions and action sanctions in criminal law and the relevance of qualifying chemical castration sanctions as action sanctions in criminal law. Through normative research, using various literature and related laws and regulations, the author seeks to dissect the problem. The results of this paper show that criminal sanctions lead to suffering whereas action sanctions lead to recovery, and make the sanctions of chemical castration acts have differed from the main reason for actions in criminal law and are irrelevant to be applied today because they lead to more of an expulsion that can give rise to the existence of a double punishment.